SHORT TERM in vitro PRESERVATION OF COCONUT SEED MATERIAL: A METHOD TO FACILITATE FIELD COLLECTION AND TRANSPORT OF COCONUT GERMPLASM - S.M. Karunaratne (International Coconut Community Journal, 1988)
High cost of transport and the short storage fife of recalcitrant seednuts are two major obstacles to the effective field collection and exchange of coconut germplasm. An in vitro method involving the culture of zygotic embryos of coconut was developed to overcome these problems. The excised embryos were initially subjected to a slow growth phase by culturing in an agar based medium containing nutrients barely sufficient for their survival. After 2, 3 and 5 months in this medium, the embryos were transferred to the gerinination or the development medium for resumption of growth and plant development. 53% of the zygotic embryos preserved in this manner for a period of 2 months produced normal plants when transferred to the gennination medium. The percentage germination dropped to 32 after 5 months storage in the survival medium. The prolonged low temperature storage of cultures (100 and 40C for three months), caused irreversible damage to the coconut embryos and no plants were formed when transferred to the germination medium. The advantages of the technique are that a large number of 'seednuts' can be transported free of pests in a small container and requires no change in the culture medium during the preservation period. Unlike the germination medium, the survival medium is agar based and hence the risk of containination is low. The non gerridnators can be identified and rejected prior to the germination phase.